The influence of the addition of crumb tire rubber on the shear strength parameters of colliery spoil - Wojtaszek, Robert; Gruchot, Andrzej (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
The article presents the results of research on the influence of a crumb rubber additive on the mechanical properties of a colliery spoils composite. The analysis covered compaction parameters (optimum moisture content, maximum dry density of solid particles) and shear strength parameters (angle of internal friction, cohesion) for composites containing 5%, 10%, and 20% crumb rubber. Compaction parameters were determined using the Proctor apparatus at a compaction energy of 0.59 J·cm−3 . Shear strength parameters were measured in a direct shear apparatus on samples with a cross-sectional dimension of 12×12 cm and a height of 2.9 cm. Soil samples were sheared with and without water saturation at a rate of 0.1 mm·min−1 until 15% horizontal deformation was achieved. The results indicate that the addition of crumb rubber decreases the maximum dry density of solid particles and increases the optimum moisture content, thereby impairing the material compactibility. For shear strength, complex relationships were observed: a small addition of crumb rubber (5–10%) improves cohesion by up to 30%, while a higher content (20%) significantly reduces it, along with the angle of internal friction. Water saturation of the samples further decreases the strength parameters, particularly with large crumb rubber additions. The optimal crumb rubber addition ranged from 5 to 10%, yielding the best values of the angle of internal friction and cohesion. The research results highlight the high potential for using colliery spoils composites with crumb rubber in earthworks, provided that the component proportions are appropriately selected.